Aplikasi Pembelajaran Biologi Berbasis Augmented Reality pada Materi Tumbuhan untuk Siswa Kelas XI - Nur, Jabal; Israwan, LM. Fajar; Ardyanti, Asni (JURNAL INFORMATIKA, 2025)
The rapid development of digital technology in the past decade has driven transformation across various sectors, including education. One emerging technology with strong innovative potential is Augmented Reality (AR), which enables the integration of virtual objects into real environments in real time. Although AR has been widely applied in industry, entertainment, healthcare, and gaming, its implementation in high-school biology learning remains limited. As a result, learning activities tend to be conventional, rely heavily on textbooks, and offer limited visualization of biological objects. This study aims to develop an AR-based biology learning application focused on plant structure materials for Grade XI students, supporting teachers in presenting three-dimensional models of leaf, stem, root, flower, and seed tissues. The research employed the Multimedia Development Life Cycle (MDLC) consisting of six stages: concept, design, material collecting, assembly, testing, and distribution. Application development utilized Unity for system programming and Blender 3D for three-dimensional object modeling. The results indicate that the application successfully detects markers through a device camera and displays plant 3D models interactively in real time. The implementation of AR increases student engagement, enhances visual representation, and facilitates understanding of abstract biological concepts.